2017
DOI: 10.1099/jmm.0.000631
|View full text |Cite
|
Sign up to set email alerts
|

High mortality of bloodstream infection outbreak caused by carbapenem-resistant P. aeruginosa producing SPM-1 in a bone marrow transplant unit

Abstract: The predominant clone belonging to ST277 showed high mortality. Carbapenem use was the only risk factor associated with CRPa-BSI. This finding is a wake-up call for the need to improve management in BMT units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 39 publications
0
18
0
1
Order By: Relevance
“…P. aeruginosa ST277 is a clone spread throughout the Brazilian territory and related to high mortality rates [2,10,18]. A greater similarity within Brazilian strains was found when compared to ST277 genomes isolated from other countries, showing that strains from Brazil share a high number of exclusively SNPs.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…P. aeruginosa ST277 is a clone spread throughout the Brazilian territory and related to high mortality rates [2,10,18]. A greater similarity within Brazilian strains was found when compared to ST277 genomes isolated from other countries, showing that strains from Brazil share a high number of exclusively SNPs.…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that In163, rmtD and bla SPM-1 are frequently associated to ST277 [2,10,17,18]. Together, these mechanisms cause resistance to the main antimicrobials used against P. aeruginosa in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…These bacteria can harbour multiple antibiotic resistance mechanisms, leading to limited therapeutic options [4]. Recently, during an outbreak in our hospital, we conduct a casecontrol study and observed that prior use of carbapenem was the only independent risk factor for carbapenems-resistant P. aeruginosa (CRPA) BSI (P=0.043) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Carbapenem-resistant Pseudomonas aeruginosa bloodstream infection (CRPA-BSI) has been associated with high morbidity and mortality in hematopoietic stem cell transplantation (HSCT) patients. Nowadays, it is a challenge with limited therapeutic options (12). Thus, in vitro synergy studies are important to define combination therapy that can be useful to treat these infections.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in vitro synergy studies are important to define combination therapy that can be useful to treat these infections. To date, few studies evaluated antimicrobial synergy against CRPA (3 5) and the role of virulence on the high mortality associated with CRPA-BSI is controversial as well (2, 3).…”
Section: Introductionmentioning
confidence: 99%